Comparing capitalisms and taking institutional context seriously - Jackson, Gregory; Deeg, Richard (Journal of International Business Studies, 2019)
A major limitation of existing international business (IB) research remains the rather thin view of institutional context. In this retrospective, we reflect upon and highlight different strategies for overcoming de-contextualized perspectives and developing thicker conceptions of institutions drawing on comparative research. Institutions shape firm behavior not only through their direct or additive effects, but have more complex influences by moderating relationships between firm-level variables or having interactive or configurational effects related to wider sets of institutions. These views can each be extended by adopting a dynamic perspective examining how multinational enterprise (MNE) agency contributes to processes of institutional change. Ultimately, a large gap remains in taking institutions seriously that IB scholars could fill by developing middle-range theories that link and compare how particular kinds of institutions or institutional configurations influence particular kinds of MNE activities.